INTEGRATING SOCIAL-EMOTIONAL LEARNING (SEL) INTO A HYBRID MIDDLE SCHOOL CURRICULUM TO FOSTER DIGITAL WELLBEING AND RESILIENCE - Helen Nabirye; Ronald Muwanguzi; Deborah Wanyama (Yayasan Adra Karima Hubbi, 2025)
The increasing integration of digital technologies in middle school education has transformed how students learn, interact, and develop their emotional intelligence. However, prolonged digital engagement in hybrid learning environments often leads to emotional fatigue, decreased empathy, and reduced digital wellbeing among adolescents. Addressing this challenge requires embedding Social-Emotional Learning (SEL) within hybrid curricula to enhance students’ resilience, empathy, and self-regulation in digital contexts. This study aims to design and evaluate an SEL-integrated hybrid curriculum model that promotes digital wellbeing and emotional balance among middle school students. A mixed-method design was employed, combining quasi-experimental and qualitative approaches. The participants included 120 students from three hybrid middle schools in Indonesia. Quantitative data were gathered through pre- and post-intervention surveys using a validated SEL and digital wellbeing scale, while qualitative insights were collected from focus group discussions and classroom observations. Data were analyzed using paired-sample t-tests and thematic coding. Results revealed significant improvements in students’ emotional awareness (p < 0.01), empathy (p < 0.01), and digital self-regulation (p < 0.05). Qualitative findings further indicated that integrating SEL practices such as mindfulness exercises, reflective journaling, and collaborative digital storytelling enhanced students’ resilience and strengthened teacher-student relationships in hybrid settings. The study concludes that embedding SEL into hybrid curricula effectively fosters holistic learning, digital citizenship, and emotional stability. This framework offers a scalable model for schools seeking to balance academic achievement with psychological wellbeing in digitally mediated education.